Grain yield and competitive ability against weeds in modern and heritage common wheat cultivars are differently influenced by sowing density - Lazzaro, Mariateresa; Costanzo, Ambrogio; Farag, Dalia Hosam; Bàrberi, Paolo (Italian Journal of Agronomy, 2017)
Sowing density can have a strong impact on crop stand development during wheat growing cycle. In organic and low-input agriculture, and therefore with minimum or nil use of chemical herbicides, increased sowing density is expected to affect not only grain yield but also weed suppression. In this study we tested, under Mediterranean conditions, six common wheat cultivars (three modern and three heritage) and two three-component mixtures (arranged by combining the three modern or the three heritage cultivars). The different crop stands were tested at sowing densities of 250 (low) and 400 (high, similar to standard sowing density used by local farmers) viable seeds m–2 for two growing seasons. We did not detect a significant effect of crop stand diversity (single cultivars vs mixtures) on grain yield and weed suppression. Differences were ascribed to type of cultivars used (heritage vs modern). Compared to high sowing density, in modern cultivars grain yield did not decrease significantly with low sowing density, whereas in heritage cultivars it increased by 15.6%, possibly also because of 21.5% lower plant lodging. Weed biomass increased with low sowing density both in heritage and modern cultivar crop stand types. However, heritage crop stands had, on average, a lower weed biomass (56%) than modern crop stands. Moreover, weed biomass in heritage crop stands at low density (6.82±1.50 g m–2) was lower than that of modern cultivars at the same sowing density (15.54±3.35 g m–2), confirming the higher suppressive potential of the former. We can conclude that lower sowing density can be advisable when using heritage crop stands as it keeps productivity while decreasing plant lodging and maintaining weeds under control.